2012
DOI: 10.1080/10438599.2011.639979
|View full text |Cite
|
Sign up to set email alerts
|

Do financial constraints threat the innovation process? Evidence from Portuguese firms

Abstract: Abstract:This paper broadly addresses the financing problems of the innovation process, by analysing the extent to which financial constraints hinder firms' investment in R&D and innovation, as well as investigating the role of public financial support in alleviating such constraints. In order to overcome the problems associated with measuring financial constraints, we make use of both indirect and direct measures of constraints. Our findings suggest that while financial constraints have a perverse effect upon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(40 citation statements)
references
References 49 publications
1
36
0
Order By: Relevance
“…In the absence of financing constraints, R&D investment will not be sensitive to financial factors. More recently, the studies have adapted direct approach by supplementing financial statement information with the other instruments like credit ratings and direct surveys in identifying the potentially financially constrained firms Savignac, 2008;Silva & Carreira, 2012). However, there are some apprehensions about direct approach as it may lead to biased results since respondents may overstate 'lack of finance' if they are investing more in R&D projects (Czarnitzki & Hottenrott, 2010).…”
Section: Theoretical Underpinnings and Literature Reviewmentioning
confidence: 97%
“…In the absence of financing constraints, R&D investment will not be sensitive to financial factors. More recently, the studies have adapted direct approach by supplementing financial statement information with the other instruments like credit ratings and direct surveys in identifying the potentially financially constrained firms Savignac, 2008;Silva & Carreira, 2012). However, there are some apprehensions about direct approach as it may lead to biased results since respondents may overstate 'lack of finance' if they are investing more in R&D projects (Czarnitzki & Hottenrott, 2010).…”
Section: Theoretical Underpinnings and Literature Reviewmentioning
confidence: 97%
“…Therefore, considering the effects on direct measures of innovation output can complement the findings of these studies and contribute to a better assessment of the overall impact of financing difficulties 1 See Czarnitzki and Hottenrott (2010) for an overview of the empirical literature. 2 A negative relation between financial constraints and innovation has been shown, for example, in French manufacturing firms (Savignac, 2008), in German manufacturing firms (Hottenrott and Peters, 2012), in Portuguese firms (Silva and Carreira, 2012) and in transition economies (Gorodnichenko and Schnitzer, 2013;Männasoo and Meriküll, 2014). on innovation performance.…”
Section: Introductionmentioning
confidence: 99%
“…By analyzing the impact of the measure of self-evaluation of constraints on investment in R&D, Silva and Carreira (2012) found that, when the endogeneity problem associated with this variable is taken into consideration, the financial constraints significantly mitigate the amount invested in R&D. These authors showed that innovation in a broad sense is greatly hampered by financial constraints. Nanda and Nicholas (2014) tried to trace the trajectory of innovation in different countries (based on the history of patents), and they found that a slump in the availability of external bank financing had, not only, an impact on the rate of innovation, but it had also changed the trajectory of innovation from experimental and radical innovations to incremental innovations, which means that disruption of the availability of capital has real effects in terms of innovation, noting that companies that were awarded quickly are the ones with high capital intensive.…”
Section: The Innovation and Financial Constraints: A Recent Review Ofmentioning
confidence: 98%
“…De Mel, McKenzie, and Woodruff (2009), Ang (2010), and Silva and Carreira (2012) presented three different studies on the relationship between access to financial resources and innovation. These authors demonstrated that access to finance is positively correlated with the ability to innovate, however, this correlation may also reflect unmeasured productivity attributes of the company that are correlated with both its ability to innovate and its decision to receive a loan.…”
Section: The Innovation and Financial Constraints: A Recent Review Ofmentioning
confidence: 99%